Pay agreement for Civic Restaurant and School Meals Staff, 1948 (pg. 2) (United Kingdom, 1948)
1948 1945-1960 "Pay agreement for Civic Restaurant and School Meals Staff, 1948 (pg. 2)" [HFR0054b], 1948 This National Union of Public Employees leaflet includes details of the first national agreement for women renamed Civic Restaurants in 1946.